Bruxism in Movement Disorders: A Comprehensive Review. Issue 7 (14th April 2016) - Ella, Bruno; Ghorayeb, Imad; Burbaud, Pierre; Guehl, Dominique
Abstract: Bruxism is an abnormal repetitive movement disorder characterized by jaw clenching and tooth gnashing or grinding. It is classified into two overlapping types: awake bruxism (AB) and sleep bruxism (SB). Theories on factors causing bruxism are a matter of controversy, but a line of evidence suggests that it may to some extent be linked to basal ganglia dysfunction although so far, this topic has received little attention. The purpose of this article was to review cases of bruxism reported in various movement disorders. The biomedical literature was searched for publications reporting the association of bruxism with various types of movement disorders. As a whole, very few series were found, and most papers corresponded to clinical reports. In Parkinsonian syndromes, AB was rarely reported, but seems to be exacerbated by medical treatment, whereas SB is mainly observed during non‐REM sleep, as in restless leg syndrome. AB is occasionally reported in Huntington's disease, primary dystonia, and secondary dystonia; however, its highest incidence and severity is reported in syndromes combining stereotypies and cognitive impairment, such as Rett's syndrome (97%), Down syndrome (42%), and autistic spectrum disorders (32%). Taken as a whole, AB seems to be more frequent in hyperkinetic movement disorders, notably those with stereotypies, and is influenced by anxiety, suggesting an involvement of the limbic part of the basal ganglia in its pathophysiology.